2015
DOI: 10.1371/journal.pone.0135422
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of Auditory Sensory and Cognitive Learning in Typically Developing Children

Abstract: Despite the well-established involvement of both sensory (“bottom-up”) and cognitive (“top-down”) processes in literacy, the extent to which auditory or cognitive (memory or attention) learning transfers to phonological and reading skills remains unclear. Most research has demonstrated learning of the trained task or even learning transfer to a closely related task. However, few studies have reported “far-transfer” to a different domain, such as the improvement of phonological and reading skills following audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…Critically, the amenability of Selective auditory attention performance to training is not limited to these highly-selective groups. Improvement in Selective Attention performance has been demonstrated after a 4-week dichotic-listening training program in healthy adults (Soveri et al, 2013), and similar training effects have been reported in typically developing children (Murphy, Moore, & Schochat, 2015), as well as children with dyslexia (Helland et al, 2018). These findings point to the flexible nature of auditory Selective Attention, which can be improved through formal training programs and as well as frequent practice (Mishra, de Villers-Sidani, Merzenich, & Gazzaley, 2014).…”
Section: The Comparison Between Selective and Distributed Attention Isupporting
confidence: 54%
“…Critically, the amenability of Selective auditory attention performance to training is not limited to these highly-selective groups. Improvement in Selective Attention performance has been demonstrated after a 4-week dichotic-listening training program in healthy adults (Soveri et al, 2013), and similar training effects have been reported in typically developing children (Murphy, Moore, & Schochat, 2015), as well as children with dyslexia (Helland et al, 2018). These findings point to the flexible nature of auditory Selective Attention, which can be improved through formal training programs and as well as frequent practice (Mishra, de Villers-Sidani, Merzenich, & Gazzaley, 2014).…”
Section: The Comparison Between Selective and Distributed Attention Isupporting
confidence: 54%
“…Students are directed through procedural learning activities and problems that stimulate curiosity to find various information as an alternative solution. Various learning experiences experienced form the personality of students to be able to succeed in the work that will be undertaken in accordance with the profile of graduates [2], [4], [7], [8], [23]. Thus, the success of universities in producing graduates who have the ability and skills in accordance with the profile of graduates is more effective with learning tools based on academic success skills.…”
Section: Division Of Groups Based On Gainmentioning
confidence: 99%
“…This increase is owned by Students by familiarizing themselves with the use of learning tools based on academic success skills. Students are trained in developing thoughts to be able to achieve metacognition knowledge [3], [6], [8], [13], [18], [19], [25], [26], [33]. By having metacognition knowledge, Students can achieve success in planning and various considerations taken to live life.…”
Section: Division Of Groups Based On Gainmentioning
confidence: 99%
“…Compressed speech tests are often used in studies on auditory training (22)(23)(24) . Although the test developed by Rabelo and Schochat (20) does not present standardization validated for Brazilian children, in the present study, its use was only to measure the effectiveness of auditory training with PER, comparing the results found in pre-training and post-training assessments.…”
Section: Pilot Studymentioning
confidence: 99%